Hubungan antara Kecerdasan Adversitas dengan Grit Akademik Mahasiswa UIN Antasari yang Kurang Mampu - Desiana, Yola Lita (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
Adversity quotient is a person's ability to respond, face, survive and change one's response in seeing a difficulty that is in front of him. Success can be achieved by consistency of interest and persistence in trying to achieve long-term goals is defined as grit. The purpose of this study was to find out whether there is a relationship between adversity quotient and academic grti of students at UIN Antasari Banjarmasin who are less fortunate. The research method used is quantitative with a correlational approach. The results of the correlation test obtained a significance value of 0.000 <0.05 so that the hypothesis proposed was acceptable. The results of the hypothesis test show that the r count is 0.641, which means that the relationship between variables has a strong level of relationship.